THE STUDY OF CODE SWITCHING OF ENGLISH TEACHING LEARNING OF AN-NASYIIN ENGLISH COURSE IN INTERMEDIATE CLASS - Ririn, Siti Qamariyah (Universitas PGRI Palembang, 2025)
Student understanding plays a crucial role in the teaching and learning process. In addition to the teaching methods applied by the teacher, the language used in the classroom can significantly aid students in grasping the subject matter, especially in language learning such as English. The language used during lessons greatly influences how well students comprehend the material presented by the lecturer. When the teacher uses English entirely throughout the lesson, some students may struggle to follow and understand the content. However, in practice, some lecturers adopt a bilingual or multilingual approach, often applying the concept of code-switching. This makes it easier for students to understand the material. This study employed a qualitative approach through interviews and classroom observations to collect data. The findings reveal various types and purposes of code-switching used during classroom instruction. The main reason for using code-switching is to provide clearer explanations and help students better understand the learning material.